FAKTOR PENDORONG KEBERLANJUTAN PENGELOLAAN SAMPAH RUMAH TANGGA BERBASIS MASYARAKAT DI KOTA BALIKPAPAN DAN BOGOR - Nino Heri Setyoadi (Jurnal Sains & Teknologi Lingkungan, 2018)
AbstractSolid waste reduction and handling efforts require full community participation. Governments and stakeholders continue to improve solid waste reduction and handling. From 71 million tons of waste was produced, it was only capable of carrying out waste reduction of 6.5 million tons (10%) in 2015. The 3 R movement also has not shown significant result, it was only 7.5% of waste that is processed into compost and recycle, 10% still in the grave in the ground, 5% was burned, and 8.5% unmanaged. As much as 69% of the total waste was dumped into the waste landfill. For that we need an assessment the driving factors of sustainability of community-based solid waste management. This paper aims to analyze the driving factors of sustainability community-based solid waste management in the cities of Bogor and Balikpapan. The approach used in the form of qualitative research methods through the process of description, tendency, and interpretation. The results showed that there are 6 (six) driving factors that play a major role in the sustainability of community-based solid waste management in the cities of Bogor and Balikpapan. The driving factors include the role of community leaders, economic benefits, social benefits, environmental benefits, the management network, and the stimulation and facilitation of local government.Â Keywords: driving, sustainability, domestic waste, and community participation